Key ideas in trusts law / Nicholas J. McBride. - McBride, Nicholas J. (Key ideas in law., 2023)
This resource presents students with a short and concise introduction to trusts law and presents the trust as a mechanism to manage wealth. It is split into five chapters which address key concepts underpinning the study of the law of trusts.